THE EFFECT OF NON-PHYSICAL WORK ENVIRONMENT AND WORK DISCIPLINE ON THE PERFORMANCE OF EMPLOYEES OF PERUMDA TIRTA JATI DRINKING WATER CIREBON REGENCY - Varidha Indry Fatmawati; Lisa Harry Sulistiyowati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine how the non-physical work environment and work discipline partially and simultaneously affect the work outcomes of employees at the Tirtajati Drinking Water PDAM company in the Cirebon Regency area. This study included all employees of the company using the saturated sample method to cover all 75 employees of the company PERUMDA drinking water Tirtajati, Cirebon regency. The results showed that the non-physical work environment had a significant positive influence on employee performance (t-calculated value > t-table value, 2,753 > 1,993) similarly, work discipline had a significant positive influence on employee productivity (t-value calculated > t-table value, 3,978 > 1.993) and (F-value > F-table value), 23.667 > 3.12). All parts and simultaneous test results give significant values below 0.005 or 0.000, which is equivalent to a significance level of 0.05.